Kajian Kesesuaian Wisata Selam dan Snorkeling di Perairan Tulamben, Karangasem, Bali - Sari, Nur Asni Puspita; Putra, I Dewa Nyoman Nurweda; Dirgayusa, I Gusti Ngurah Putra (Journal of Marine and Aquatic Sciences; Vol 3 No 1 (2017), 2017)
Tulamben village located in the district of Kubu, Karangasem regency, has developed into one of the maritime destination, especially diving and snorkeling. Based on data from the Department of Culture and Tourism of Bali, the average number of tourists coming to Tulamben in 2012-2014 reached 94,253 tourists. This condition makes the tourism has grown into a major economic support local communities in the Tulamben. Economic growth without being accompanied by an appropriate management plan will certainly produce a negative impact on coastal and marine resources to be a major asset for the growth. Various forms of management that allows to be applied has been identified in an effort to support the sustainability of the ecological, economic and socio-cultural community. This study was conducted to analyze the suitability of diving and snorkeling, coral identification were examined using LIT (Line Intercept Transect) methods while the abundance of reef fish species assessed using visual underwater cencus (UVC). Analysis of the data used is the analysis of the potential reef and suitability. Determination of the suitability of the area as a tourist diving and snorkeling analysis using matrix parameters to consider the appropriateness of the ecological conditions and water quality conditions of the four classifications. Cover of live coral communities ranged between 16.26% -52.48% with a diversity of reef fish species ranged between 11-44 types. Travel suitability index (IKW) category snorkeling and diving are included in the category is not appropriate (N) and the corresponding (S2).
Keywords: tourism suitability; diving; snorkeling; Tulamben